IMPROVING PHYSICS LEARNING OUTCOMES WITH DIFFERENTIATE LEARNING ON VIBRATION AND WAVES OF CLASS VIII STUDENTS AT MTS AL-WASHLIYAH GEDUNG JOHOR MEDAN - Andreana, Rifa Risqita; Warty, Yuni ((IPER) Indonesian Physics Education Research, 2023)
This study aims to improve students' physics learning outcomes by applying differentiation learning to vibration and wave material. The population in this study were class VIII students of MTs Al-Washliyah Gedung Johor, Medan, for the 2022/2023 academic year. The sample in this study was class VIII-A as the control class totaling 40 students who were given conventional learning, and class VIII-B as the experimental class totaling 39 students who were given differentiated learning. The sampling method used was quasi-experimental and used a pretest-posttest control group design. Data on physics learning outcomes were collected using observation instruments and knowledge tests in the form of 10 essay questions. The increase in students' physics learning outcomes was seen by comparing the average hypothesis test scores customarily distributed and homogeneous in both classes. Based on the outcomes, the conclusion stated that the application of differentiated learning on vibration and wave material could significantly improve student learning outcomes.